2016
DOI: 10.7196/sajog.2016.v22i2.1048
|View full text |Cite
|
Sign up to set email alerts
|

Patient knowledge and intention to use the intrauterine contraceptive device (IUCD) at a tertiary level hospital.

Abstract: Background. The intrauterine contraceptive device (IUCD) is a highly effective and safe method of contraception. Prevention of unwanted pregnancies has made its use a matter of national priority in certain countries. Despite numerous advantages and suitability, the uptake of the IUCD is poor. Patients in South Africa (SA) seem to lack knowledge regarding this contraceptive. Objectives. To determine the quantity and quality of knowledge about the IUCD, and to evaluate its acceptability for future use. Methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 7 publications
0
23
0
Order By: Relevance
“…[2] Study done in primary care family planning clinics in Cape Town showed that the knowledge of the IUCD as the contraceptive method was very poor, despite its availability it was underused and not a preferred method to prevent pregnancy, shows that 41% of women had heard about this method but that only 4% had ever used it. [3] The study done in South Africa showed that there was lack of knowledge among the participants in the study regarding IUCD; therefore, despite the availability of the IUCD in SA clinics and hospitals, its uptake was poor. Awareness of this method seemed to have improved over the past few years but the knowledge was considerably lacking.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Study done in primary care family planning clinics in Cape Town showed that the knowledge of the IUCD as the contraceptive method was very poor, despite its availability it was underused and not a preferred method to prevent pregnancy, shows that 41% of women had heard about this method but that only 4% had ever used it. [3] The study done in South Africa showed that there was lack of knowledge among the participants in the study regarding IUCD; therefore, despite the availability of the IUCD in SA clinics and hospitals, its uptake was poor. Awareness of this method seemed to have improved over the past few years but the knowledge was considerably lacking.…”
Section: Introductionmentioning
confidence: 99%
“…2018; Callahan et al. 2019; Van Der Westhuizen and Hanekom 2016; Ndegwa et al. 2014; Jairaj and Dayyala 2016; Eva et al.…”
Section: Resultsmentioning
confidence: 99%
“…2016; Scavuzzi, Souza, and Amorim 2016; Mahlalela and Maharaj 2015; Jairaj and Dayyala 2016; Hayes and Kilbourne‐Brook 2016b; Kyamwanga et al. 2014; Mathenjwa and Maharaj 2012; Van Der Westhuizen and Hanekom 2016). Many women saw the ability to use a method while breastfeeding as a positive factor (Huber‐Krum et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In African countries, knowledge of IUCD ranged from 24% to 84% in various studies. [ 12 13 14 ] This implies that promotion and awareness campaigns of family planning methods needs to be upscaled by the health department.…”
Section: Discussionmentioning
confidence: 99%